Polythene mulching in rubber seedling nursery - Lakshmanan R; Mani Jacob; Mathew M; Pothen J; Punnoose K I (Indian Journal of Natural Rubber Research, 1995)
The feasibility of using polythene films as mulch in rubber seediling nursery was investigated. Field studies were conducted with three types of clear polythene films, conventional plant mulch and an unmulched control. The polythene mulches were topped with a thin layer of soil of over 5 cm thickness. Mulching significantly enhanced seedling growth. Polythene-mulched plots recorded 15.5 to 28.9 per cent increase in plant diameter over the unmulched plots and compared favourably with plant mulch. The soil moisture content in the surface 0-15 cm soil layer with polythene mulching was 87-113 per cent more than that in the unmulched plots during extreme dry weather conditions, while the increase with plant mulching was only 50 per cent. The extent of weed control achieved with polythene mulching was 84 to 90 per cent and that with plant mulching 56.9 per cent, over the unmulched plots. Mulching with polythene sheets did not increase absolute soil temperature over the conventional plant mulches. Soil temperature fluctuations were also minimised due to mulching.
Keywords: Mulching; Plant mulch; Polythene film; Rubber nursery; Soil temperature; Weed control